2017
DOI: 10.1055/s-0043-122277
|View full text |Cite
|
Sign up to set email alerts
|

Dekolonisation bei Nachweis von Methicillin-sensiblen Staphylococcus aureus bei Mitarbeitern einer neonatologischen Intensivstation

Abstract: Various reasons might explain the difficulties of decolonization such as the challenge of managing decolonization at home, inhibitory factors as well as inconsistent performance of decolonization measures. Additionally, differences between the preparations for the nasal decontamination may be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Most of the studies were based in high-income countries (9 out of 16) and located in Europe (4 out of 16) and the Western Pacific Region (3 out of 16) ( Figure 2 and Table S3 ). HCWs were the most studied group (8 out of 16) [ 29 , 31 , 34 , 35 , 39 41 , 44 ], followed by environmental samples (6 out of 16) [ 30 , 32 , 35 , 37 , 38 , 43 ] and neonate mothers (4 out of 16) [ 31 , 33 , 36 , 42 ]. The reasons for testing for MRSA colonization in the included studies vary significantly, ranging from routine surveillance to specific medical interventions and responses to identified issues, such as pre- and posthand hygiene interventions, cleaning measures, admission due to preterm birth, and responses to ongoing MRSA detections in neonates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies were based in high-income countries (9 out of 16) and located in Europe (4 out of 16) and the Western Pacific Region (3 out of 16) ( Figure 2 and Table S3 ). HCWs were the most studied group (8 out of 16) [ 29 , 31 , 34 , 35 , 39 41 , 44 ], followed by environmental samples (6 out of 16) [ 30 , 32 , 35 , 37 , 38 , 43 ] and neonate mothers (4 out of 16) [ 31 , 33 , 36 , 42 ]. The reasons for testing for MRSA colonization in the included studies vary significantly, ranging from routine surveillance to specific medical interventions and responses to identified issues, such as pre- and posthand hygiene interventions, cleaning measures, admission due to preterm birth, and responses to ongoing MRSA detections in neonates.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Greece from January 2014 to December 2018 among general doctors and nurses reported a prevalence of 16.22% (6 out of 37 participants, 95% CI: 6.19-32.01) [ 34 ]. Two German studies conducted in February-August 2010 and 2016 found a proportion of 1.25% (95% CI: 0.15-4.44) and 1.56% (95% CI: 0.19-5.53), respectively [ 39 , 41 ]. In India, a study conducted between July and August 2013 among general doctors and nurses tested MRSA prevalence pre- and posthand hygiene intervention [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 16 studies, 9 were noncomparative, i.e., they used OCT among persons identified as S. aureus carriers and described effects on carriage rates or the success of decolonization without comparing OCT to the effects of other antiseptics or antibiotics [21,24,25,[27][28][29][30][31][32]. The interventions were too heterogeneous to compare the decolonization success rates of these studies because of the variation in the treatment regimens, the microbiological techniques to control the success of the therapy, and the time intervals in which patients were followed up after the end of the treatment.…”
Section: S Aureus Decolonization Infection Prevention and Nosocomial ...mentioning
confidence: 99%